ISO 9001 or ISO 17025 : what is more important for the metrology laboratory - Barradas, José (2011)
In the last decade, the number of Portuguese companies with quality certiÞ cation has increased, as is the case in most countries. According to the ISO 9001 standard all the certiÞ ed companies should calibrate their measuring equipment. By doing so, companies can guarantee, with rigor and quality, its measurement and use reliable data for monitoring the quality of its products and its improvement. However, a metrology laboratory is not required to hold an ISO 9001 certiÞ cation or ISO 17025 accreditation. In this moment, there are companies that have metrology laboratories to conduct an internal check of their measuring equipment. These companies have their quality management systems (QMS) certiÞ ed according to the ISO 9001 standard and so all its departments and sub-departments must also comply with the requirements of this standard. On the other hand there are companies with ISO 17025 accredited laboratories. Usually these companies are independent and his metrology laboratory is essentially to perform the calibration service to national companies who use their services to make the calibration of its measuring devices. These labs can be inserted into a company which does not have their QMS certiÞ ed by any national or international standard. Finally, there are companies that have their QMS certiÞ ed to ISO 9001 and also its metrology laboratory accredited by ISO 17025. In this case the metrology lab must comply with the requirements of both standards. Thus, the aim of the research project is to analyze, in Portugal, the importance level of ISO 9001 and ISO 17025 standards for a metrology laboratory to reach the quality.